Mathematickles! : poems - Franco, Betsy; Salerno, Steven (New York : Aladdin Paperbacks, 2003)
A collection of poems written in the form of mathematical problems and grouped according to seasonal themes.
Five Owls
School Library Journal starred
Wilson's Children
Book Links (A.L.A.), November 2004
Booklist, May 2003
Bulletin (Center for Children's books), June 2003
Keywords: Children's poetry, American; Mathematics -- Juvenile poetry; American poetry; Mathematics -- Poetry; Seasons -- Poetry; Visual poetry; American poetry; Mathematics -- Poetry; Seasons -- Poetry; Visual poetry